Cell-type expression and activation by light of neuropsins in the developing and mature Xenopus retina - Man, Lawrence L. H.; Storey, Samuel S.; Bertolesi, Gabriel E.; McFarlane, Sarah (Frontiers in Cellular Neuroscience, 2023)
Photosensitive opsins detect light and perform image- or nonimage-forming tasks. Opsins such as the “classical” visual opsins and melanopsin are well studied. However, the retinal expression and functions of a novel family of neuropsins are poorly understood. We explored the developmental time-course and cell-type specificity of neuropsin (opn5, 6a, 6b, and 8) expression in Xenopus laevis by in situ hybridization and immunohistochemistry. We compared the Xenopus results with publicly available single cell RNA sequencing (scRNA-seq) data from zebrafish, chicken, and mouse. Additionally, we analyzed light-activation of neuropsin-expressing cells through induction of c-fos mRNA. opn5 and opn8 expression begins at stage 37/38 when the retinal circuits begin to be activated. Once retinal circuits connect to the brain, opn5 mRNA is distributed across multiple retinal cell types, including bipolar (~70-75%), amacrine (~10%), and retinal ganglion (~20%) cells, with opn8 present in amacrine (~70%) and retinal ganglion (~30%) cells. opn6a and opn6b mRNAs emerge in newborn-photoreceptors (stage 35), and are colocalized in rods and cones by stage 37/38. Interestingly, in the mature larval retina (stage 43/44), opn6a and opn6b mRNAs become preferentially localized to rods and cones, respectively, while newborn photoreceptors bordering the proliferative ciliary marginal zone express both genes. In zebrafish, opn6a and opn6b are also expressed in photoreceptors, while Müller glia and amacrine cells express opn8c. Most neuropsin-expressing retinal ganglion cells display c-fos expression in response to light, as do over half of the neuropsin-expressing interneurons. This study gave a better understanding of retinal neuropsin-expressing cells, their developmental onset, and light activation.